Intervention Analysis for Modeling and Forecasting Exchange Rates Rupiah Against Yen - Anjuita Anjuita; Widyanti Rahayu; Dania Siregar (Universitas PGRI Palembang, 2023)
The Rupiah exchange rate against the Yen is one of the most important exchange rates in Indonesia since the agreement between the two countries to conduct investment and trade transactions using local currency. Exchange rate movements tended to strengthen during 2019. In 2020 there was a COVID-19 intervention and there was a significant weakening. An intervention is an event that causes a sharp increase or decrease in time series data. Intervention analysis is an analysis used on the data affected by the intervention by measuring the magnitude of the change in value and the duration of the intervention. Intervention analysis research on data on the rupiah exchange rate against the yen is still very rarely done. This study aims to apply intervention analysis in modeling and forecasting the Rupiah against the Yen exchange rate by considering the impact of the COVID-19 intervention. Research shows that the COVID-19 intervention on the Rupiah exchange rate against the Yen has had a long impact with the best intervention model being ARIMA (4,2,0) with an order of intervention (0,1,0). The level of forecasting accuracy using the model is very good with a MAPE value of 2.69%.